Wild Edible Plants and their Consumption Pattern of Dharampur and Kaprada Taluka in South Gujarat - Chaudhari, A. Z.; Thakor, A. B. (Indian Forester, 2023)
The ethnobotanical survey has been carried out to collect information about wild edible plants in Dharampur and Kaprada taluka of the Valsad district in Gujarat. Also, the study narrates different patterns to use the parts of plants. The field survey was conducted using a semi-structured questionnaire and personal interviews with the local informants. During the survey, 42 genera were recorded from 32 families. The analysis about the intensity of use of the different parts of plants has been formatted.